1999
DOI: 10.3109/13697139909038060
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of simvastatin and estrogen-progestin therapy compared with each therapy alone for hypercholesterolemia in postmenopausal women

Abstract: For postmenopausal women with hypercholesterolemia, use of a statin in combination with continuous combined oral estrogen and progestin therapy can result in a more cardioprotective lipoprotein-lipid profile than that achieved with either therapy used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Our results are compatible with the observation of a greater HT impact on TC and LDL-C on hyper-than in normo-lipidemic women 29 . We observed no modification in HDL-C levels, with LLA or HT (except for transdermal opposed estradiol, see below) which is in agreement with previous RCTs showing no modification 26,27 , or of low amplitude, either positive 25,27,30 , or negative 28 . Modulating effects may be less evident when HDL-C concentrations are already high (2/3 of women in our study had HDL-C higher than 1.55 mmol/l) or for women with lower clinical risk 30,31 .…”
Section: Impact Of Lla Treatment Or/and Ht On Ldl-c Level Risksupporting
confidence: 80%
See 1 more Smart Citation
“…Our results are compatible with the observation of a greater HT impact on TC and LDL-C on hyper-than in normo-lipidemic women 29 . We observed no modification in HDL-C levels, with LLA or HT (except for transdermal opposed estradiol, see below) which is in agreement with previous RCTs showing no modification 26,27 , or of low amplitude, either positive 25,27,30 , or negative 28 . Modulating effects may be less evident when HDL-C concentrations are already high (2/3 of women in our study had HDL-C higher than 1.55 mmol/l) or for women with lower clinical risk 30,31 .…”
Section: Impact Of Lla Treatment Or/and Ht On Ldl-c Level Risksupporting
confidence: 80%
“…When taken together, HT and LLA globally were not associated with major additional effects compared to LLA alone, as observed in small RCTs with hyperlipidemic women [24][25][26]28 . However, in women using EPT and LLA, we observed significant differences when comparing transdermal to oral estradiol, with higher HDL-C level for women also treated with fibrate, but lower TG and higher LDL-C levels, for those treated with statin.…”
Section: Impact Of Lla Treatment Or/and Ht On Ldl-c Level Riskmentioning
confidence: 64%
“…Hormone replacement therapy (HRT) is the effective regimen to prevent these diseases in postmenopausal women [5,6]; however, it is accompanied by an increased risk of unfavorable outcomes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Serum bonespecific alkaline phosphatase (BSALP; Alkphase-B; Metra Biosystems, Mountain View, CA, USA) was measured by using a microplate coated with an anti-BSALP monoclonal antibody. Serum intact osteocalcin (OC) was measured by using a sandwich enzyme immunoassay (EIA) that uses polyclonal antibodies against 20 N-terminal residues (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and against 7 C-terminal residues (amino acids 43-49; Biomedical Technology, Stoughton, MA, USA). Urine samples were collected from a second voiding at the same time as blood collection, and they were stored at -20°C.…”
Section: Effects Of Isoflavone and Walking On Bone And Fat Massmentioning
confidence: 99%
“…(1)(2)(3)(4) Hormone replacement therapy (HRT) is an effective regimen that prevents these diseases in postmenopausal women. (5,6) However, the HRT trial carried out by the Women's Health Initiative (WHI) found that long-term use of HRT (follow-up, 5.2 years) poses serious risks and may increase the risk of heart attack and stroke. (7) Follow-up studies with the WHI will likely provide insight as to whether the increased risks and benefits of HRT therapy decline after the end of the therapy and the time at which this decline occurs as well as evaluation of the dose.…”
Section: Introductionmentioning
confidence: 99%